Electrochemical behavior of the commercial Ni-Cr-based alloy Wiron 99 in 0 .05 mol/L sulphuric media - Ernesto Peláez; W.D. Müller (Revista CENIC Ciencias Químicas, 2000)
During the last two decades, Ni-Cr-based alloys have become frequently used in dental applications as an alternative to alloys based on noble metals, because their mechanical properties are best and the intrinsic cost is negligible compared to the traditional gold-based materials. The biocompatibility of metallic materials is closely related to their corrosion behavior. Corrosion and surface film dissolution are two mechanism to introduce additional ions into the human body. For this reason in this work, the corrosion behavior of five samples the commercial Ni-Cr-based alloy Wiron 99 in 0,05 moVL H2S04 solution have been studied by means of open circuit potential time measurements, potentiodynamic polarization curves, chemical analysis of the solutions after exposure and SEM studies. A special mini-cell was used for open circuit potential (Eo,) and polarization resistance (Rp) determination. Potentiodynamic polarization curves were made in order to calcula te the polarization resistance 20 m V around open circuit potential in the cathodic and anodic region. After ali samples were individually immersed in 0,05 moVL H2S04 solution for severa! days, micrographs of the surface were made and the concentration of Ni was determined by atomic absorption analysis. The Eoc values showed that evidently there exist two behaviors (named F- and G-behavior). This result suggests a complex dissolution process for G-behavior samples, where the Eoc values fast move with time and therefor the dissolution rate changes fast with time. However, the F-behavior samples showed a more stable dissolution rate, because the Eoc values slowly move with time.